Sudden cardiac death in athletes: big trouble, not so little Asia - Uberoi, A.; Froelicher, V. (Asian Journal of Sports Medicine, 2011)
The review by Dr. Halabchi, et al is an excellent summary and reiteration of the importance of the addition of ECG screening to the pre-participation exam (PPE) for athletic competition. To pioneer this campaign in Asia, is a noble endeavor and is no small feat. As highlighted by this review, the general consensus for enforcing ECG as a requisite for participation varies greatly by the governing bodies making the suggestions and the demographic which they represent.